METHODS OF ORIENTATION OF STUDENTS TO INNOVATIVE ACTIVITIES IN THE PROFESSIONAL DEVELOPMENT SYSTEM - Musayeva Muhabbat Eshbayevna (Web of Journals Publishing, 2024)
This scientific article presents methods for directing listeners to innovative activities in the system of professional development and methods of educational integration and the use of pedagogical technologies used in its implementation.